The Adsorptive Purification Of Low-Quality Glycerin By Biocarbon Adsorbents - Salikhanova Dilnoza Saidakbarovna; Savrieva Dilafruz Doutovna; Ismailova Mukhtasar Abdumutalib kizi; Sagdullaeva Dilafruz Saidakbarovna; Abdurakhimov Akhror Anvarovich; Karabaeva Muslima Iftikhorovna (Emerging Frontiers Library for The American Journal of Applied Sciences, 2026)
This study investigates the purification of low-quality glycerin using biocarbon adsorbents derived from cherry pits. The carbon adsorbent produced (ACCP) demonstrated superior efficacy in reducing glycerin color, decreasing it from 10 mg I₂/100 cm³ to 5 mg I₂/100 cm³, outperforming the imported coconut carbon adsorbent (ACC), which only achieved a reduction to 6 mg I₂/100 cm³. It has also been established that a carbon adsorbent with a particle size of 2-3 mm is considered optimal, as smaller particles hinder filtration, thereby increasing ash content due to the migration of fine carbon particles into the filtrate. A reduction in the acid number by 5-6 times allows for an improvement in the quality of glycerin and extends its shelf life. It has been determined that the carbon adsorbent derived from cherry pits selectively reduces the amount of free fatty acids. Initial glycerin parameters corresponded to grade T-88 specifications; however, after treatment with the synthesized adsorbents, the parameters improved to meet the D-98 standard requirements. These findings suggest that cherry pit-based adsorbents are a promising alternative for purifying glycerin in various industrial applications.